Moderate Islamic Legal Thought on Bank Interest - Putri, Dea Amanda; Pratama, Surya Bagus; Pratama, Dwi Andika; Ramadhani, Rasyha Bagas; Putri, Diva Yunika; Wohyeng, Muslim (TATHO: International Journal of Islamic Thought and Sciences, 2026)
This study focuses on describing the views of Ahmad Zahro, a professor of Islamic law in Indonesia, regarding the legal status of bank interest. This qualitative study in the form of media observation uses a content analysis approach. The primary data consists of Ahmad Zahro's YouTube content on bank interest, while the secondary data in this study uses relevant scientific literature. The results of the study show that Ahmad Zahro argues that bank interest does not always fall under the category of usury (riba), depending on the context in which the interest is applied, namely as long as there are no elements of extortion or exploitation. This study contributes to emphasizing the importance of inclusive dialogue between scholars, the community, and financial institutions to deepen understanding of the issue of bank interest.